Short Writings from Bulawayo - Morris, Jane (Book collections on Project MUSE., 2003)
Short Writings from Bulawayo won the Literature in English category at the 2005 Zimbabwe Book Publishers Association awards. It is a book of stories, poems and non-fiction pieces that are evocative of Zimbabwe's second city and its rural surroundings. The collection from 23 contributors tells of many things: of family and friendship, or fear and death, or witches and spirits, of hunger and drought, of dreams and aspirations, of leaving home and leaving Zimbabwe, of queues and loneliness, of football and bicycles and of growing old and of love. A unifying theme of many of the stories and poems.